Konsep Manajemen Pengumpulan Dana Zakat - Wardy Putra , Trisno; Naufal, Ahmad (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2019)
The focus of this research is to examine the management of zakat fund collection. Zakat is one of the Islamic social financial instruments that provide solutions to social inequalities that occur in society. Based on the results of research conducted by BAZNAS and FEM IPB, the potential for zakat in Indonesia reaches 217 trillion. However, only one percent of the existing zakat potential has been absorbed. So we need a study that discusses the management of zakat fund collection. This study uses a qualitative methodology with a literature review approach. The researcher examines the views of experts regarding the development strategies of zakat collection management. As a result, a strict regulation is needed for muzakki in paying zakat and training for zakat amil so that the collection of zakat funds can be maximized.